The combinatorial optimization problems of the discrete processes - Janušauskaitė, Nijolė (Lietuvos matematikos rinkinys, 2021)
Nonclassic combinatorial optimization problems of the discrete processes are investigated. The methodology, permitting transform there problems into equivalent typical problems, which can be solved applying dynamic programming and principle of the maximum methods, is proposed.
Keywords: dynamic programming; optimal control; maximum principle